12.5k views
3 votes
Fully condense the expression. Assume that all variables represent positive numbers. (log x -2 log y+ 3 log z) (10 points)

User Edoput
by
5.2k points

1 Answer

5 votes

Answer: The required condensed expression is
\log(xz^3)/(y^2).

Step-by-step explanation: We are given to fully condense the following logarithmic expression assuming that all variables represent positive numbers :


E=\log x-2\log y+3\log z~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We will be using the following properties of logarithms :


(i)~\log a^b=b\log a,\\\\(ii)~\log a+\log b=\log(ab),\\\\(iii)~\log a-\log b=\log(a)/(b).

Therefore, from expression (i), we get


E\\\\=\log x-2\log y+3\log z\\\\=\log x-\log y^2+\log z^3\\\\=\log(xz^3)-\log y^2\\\\=\log(xz^3)/(y^2).

Thus, the required condensed expression is
\log(xz^3)/(y^2).

User Gatlanticus
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.